(untitled) - Hipson, Peter (San Francisco, 2002)
This book teaches you about the Registry architecture and how it can be monitored and modified to suit your administrative and personal needs. --Registry coverage for users of Windows XP Home Edition, Professional, and .NET Server versions. --Experienced Windows users moving to the XP/.NET platform, power users, administrators who manage Windows XP/.NET and maintain clients, and programmers interested in manipulating the Registry from their applications will find this an essential reference. --Includes total coverage of the Windows XP/.NET registry, plus scores of undocumented tips and tricks from a Windows master.
Keywords: Windows (Computer programs)